If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = -5 + x Solving -10 = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = -5 + x + -1x Combine like terms: x + -1x = 0 -10 + -1x = -5 + 0 -10 + -1x = -5 Add '10' to each side of the equation. -10 + 10 + -1x = -5 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -5 + 10 -1x = -5 + 10 Combine like terms: -5 + 10 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 77(2x-3)+3=24 | | 8c^3+26c^2-24=0 | | 3(8-6n)=41 | | 10c^2-29c+10=0 | | 3(3y+1)=7(13-5y) | | 3(3y+1)=(13-5y) | | 5b-5x=2b+ax | | 9x-45=4x-5 | | 6u^2+35u+6=0 | | 3c^2-24c+45=0 | | 3556-4577x-5667*3456=4567 | | 2(x+2)=5(11-3x) | | 36=6(x-5) | | w^2+5w-36=0 | | 9d+7=4d+27 | | 12x-21=5x | | c^2+9c+8=0 | | 2x^4-5x^3-8x^2-5x+2=0 | | 35x^3-28x^2+15x-12=0 | | 3y=7x+5 | | r^2-8tw+4rw-2t=0 | | 8y=4x-12 | | 118-5x=40x+18 | | 2y=-5x-4 | | 9-10x=40-17x | | 1-2u-8u^2=0 | | f(-2)=-x^3-11x^2-3x+2 | | G=FN | | 4x^2=16x^2 | | 5x+5=-99-8x | | 8x^2=16x^2 | | -63x^7-7x^6=0 |